Decision Support System for Regional Health Insurance Acceptance Using Simple Additive Weighting (SAW) Algorithm Case Study in Kepatihan District, Bojonegoro Regency - Mirella Tri Ratnasari (Jurnal Mandiri IT, 2020)
Decision Support System is a computer-based information system that is intended to assist decision making by utilizing certain data and models to solve various unstructured or semi-structured problems. The purpose of this study was to measure the accuracy and precision of the SAW (Simple Additive Weighting) algorithm in selecting desktop-based candidates for Regional Health Insurance. The decision support system that is built is expected to help sub-district staff in making decisions. This decision support system is made using the Java programming language and MySQL database. The method used is Simple Additive Weighting (SAW). The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative. In this study the SAW method was chosen because this method is able to select the best alternative from a number of alternatives, in this case the alternative in question is the right to receive Regional Health Insurance based on predetermined criteria. The results of this study indicate that the decision support system using the SAW algorithm ( Simple Additive Weighting) is precise and accurate in selecting JAMKESDA recipients as seen from the percentage comparison between SAW and Manual.